Constructing Theoretical Model of Triple Helix Institutionalization Effectivity in Global Value Chains Upgrading - Hakim, Amri; Yandra, Alexander; Kabullah, M. Ichsan; Kenepri (JOELS: Journal of Election and Leadership, 2024)
Government collaboration with industry and university in innovation is a necessity to upgrade a country position in global value chains. This article aims to construct theoretical model of triple helix institutionalization effectivity. By using integrating theory method, it is modeled that the process, product, function and intersectoral upgrading determined by agent’s material capability, regime formation which create incentive structure, and trust for each parties. The quality of these independent variables produce the level collaborations as intermediate variable which consist of information and communication stream; coordination in planning and implementation; centrality of effectivity assesment.